1998
DOI: 10.1017/s0022029997002732
|View full text |Cite
|
Sign up to set email alerts
|

Bovine lactoferrin induces both mucosal and systemic immune response in mice

Abstract: Lactoferrin (Lf) is a milk iron-binding glycoprotein that plays a role in iron transport and acts as both a bacteriostatic and a growth modulating agent. The aim of this study was to investigate the nature of immune responses induced by repeated oral administration of bovine milk Lf in mice. Groups of ten female BALB/c mice were fed daily for 4 weeks with two doses of protein antigen: a low (0·05 mg/g body weight per d) or high (1 mg/g body weight per d) dose of Lf, or water as a control. A fourth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 0 publications
2
75
1
2
Order By: Relevance
“…36,37) It has also been reported that oral administration of bLF to mice increased the secretion of anti-bLF IgA and IgG in the intestinal fluid but made no difference in the serum, and it is suggested that bLF could act as an immunostimulating factor of the mucosal immune system. 38) On the other hand, it has been demonstrated that a portion of bLF is transported into blood circulation through the intestine 32,33) as previously noted. In addition, bLF is known to be comparatively robust to digestive enzymes such as pepsin or trypsin.…”
Section: Resultsmentioning
confidence: 89%
“…36,37) It has also been reported that oral administration of bLF to mice increased the secretion of anti-bLF IgA and IgG in the intestinal fluid but made no difference in the serum, and it is suggested that bLF could act as an immunostimulating factor of the mucosal immune system. 38) On the other hand, it has been demonstrated that a portion of bLF is transported into blood circulation through the intestine 32,33) as previously noted. In addition, bLF is known to be comparatively robust to digestive enzymes such as pepsin or trypsin.…”
Section: Resultsmentioning
confidence: 89%
“…In these studies, bovine lactoferrin was used to significantly enhance the current BCG vaccine. There is antigenic variation between human, bovine and murine lactoferrins (approximately 70-77% direct protein sequence match between all three molecules), which may impact responses in mice [68]. Future studies should examine responses using human or humanized lactoferrins.…”
Section: Discussionmentioning
confidence: 99%
“…19,20) Other functions might relate to host primary defense mechanisms. [21][22][23] Among them, the anti-bacterial action of LF is considered to be caused through sequestra-tion of iron required for microbial growth. 24) Recently, chemopreventive ability of bovine LF (bLF) was demonstrated in chemically induced carcinogenesis in colon, [25][26][27] esophagus 28) and lung.…”
mentioning
confidence: 99%